The Impact of Smoking Habits on Diabetes Risk: An Analysis of the Indonesia Health Survey Data - Mohamad Anis Fahmi (Ficco Public Health Journal, 2024)
Smoking is a well-established risk factor for various chronic diseases, including diabetes. However, the specific impact of smoking habits on diabetes risk within the Indonesian population remains underexplored. This study analyzes data from the Indonesia Health Survey to examine the relationship between smoking habits and the risk of developing diabetes. A cross-sectional approach was employed, utilizing nationally representative data to assess smoking behavior, diabetes prevalence, and relevant confounding variables. Logistic regression models were applied to evaluate the association between smoking status (current, former, and never smokers) and diabetes risk, adjusting for age, sex, BMI, physical activity, and dietary factors. The findings indicate a significant positive association between smoking and diabetes risk, with current smokers exhibiting a higher likelihood of diabetes compared to non-smokers. These results highlight the importance of smoking cessation programs as part of diabetes prevention strategies in Indonesia. Further longitudinal studies are recommended to establish causality and explore potential biological mechanisms underlying this relationship.